2015
DOI: 10.5812/ijem.20776
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Lipohypertrophy and Associated Risk Factors in Insulin-Treated Patients With Type 2 Diabetes Mellitus

Abstract: Background:Secondary failure of oral hypoglycemic agents is common in patients with type 2 diabetes mellitus (T2DM); thus, patients often need insulin therapy. The most common complication of insulin treatment is lipohypertrophy (LH).Objectives:This study was conducted to estimate the prevalence of LH among insulin-treated patients with Patients with T2DM, to identify the risk factors for the development of LH, and to examine the association between LH and glycemic control.Patients and Methods:A total of 1090 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
2
13

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 12 publications
(14 reference statements)
2
46
2
13
Order By: Relevance
“…Interrater reliability of reviewers regarding study relevancy was high (Kappa = 0.86). Nine studies took place in Asia, 14 in Europe, and one each in North America, Africa and a mix of different countries. The median of the mean ages was 46 years (range 6.5–63.8 years), and the median percentage of males represented in the sample was 50% (range 27.3–59.1%).…”
Section: Resultsmentioning
confidence: 99%
“…Interrater reliability of reviewers regarding study relevancy was high (Kappa = 0.86). Nine studies took place in Asia, 14 in Europe, and one each in North America, Africa and a mix of different countries. The median of the mean ages was 46 years (range 6.5–63.8 years), and the median percentage of males represented in the sample was 50% (range 27.3–59.1%).…”
Section: Resultsmentioning
confidence: 99%
“…Although reporting of lipohypertrophy was more common with BIL than glargine, these reporting rates are consistent with prospective studies evaluating the incidence and prevalence of lipohypertrophy in insulin‐treated patients. In such studies, lipohypertrophy has been reported in 29%‐76% of patients with T1D and in 4%‐56% of patients with T2D . Increased rates of lipohypertrophy may reflect slow absorption of BIL from injection sites via the lymphatic system, and a trophic effect on adipocytes resulting from a longer exposure of subcutaneous tissue to BIL.…”
Section: Injection Site Reactionsmentioning
confidence: 99%
“…In such studies, lipohypertrophy has been reported in 29%-76% of patients with T1D [51][52][53][54] and in 4%-56% of patients with T2D. 51,54,55 Increased rates of lipohypertrophy may reflect slow absorption of BIL from injection sites via the lymphatic system, 15…”
Section: Injection Site Reactionsmentioning
confidence: 99%
“…Em relação à lipohipertrofia, nesse estudo, observou-se que 17 (21,3%) pacientes referiram apresentar essa complicação, todavia, por trata-se de um dado referido e não da avaliação por meio de exame físico ou ultrassom, pode ser que este número esteja subestimado. Para avaliar lipohipertrofia, recomenda-se utilizar a inspeção e palpação (AJLOUNI et al, 2015). Destaca-se que investimentos na técnica de educação para aplicação de insulina podem reduzir a prevalência de lipohipertrofia (JI et al, 2017).…”
Section: C) Educação Tradicional Com Apoio Do Vídeo Da Cartilha Educunclassified
“…No que diz respeito aos fatores de risco modificáveis para desenvolvimento o diabetes mellitus tipo 2, a obesidade, o tabagismo e o sedentarismo têm sido aspectos amplamente estudados (MASMIQUEL et al, 2016;ŚLIWIŃSKA-MOSSOŃ;MILNEROWICZ, 2017;ZHAO, 2011 (AJLOUNI, et al, 2015;FRID et al, 2016). (NETO et al,2015).…”
Section: C) Educação Tradicional Com Apoio Do Vídeo Da Cartilha Educunclassified